Correction: Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)

Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)
Terrestrial and marine species are exhibiting distributional shifts due to climate change and resource availability. As food webs are impacted, some species have moved into areas of increased human activity, encountering anthropogenic hazards. A coastal marine species that undertakes a long migration between breeding and foraging ranges, the Eastern North Pacific (ENP) population of gray whales ( Eschrichtius robustus ) is especially vulnerable to changes. Subgroups of ENP gray whales, including the Pacific Coast Feeding Group and the (Puget) Sounders, have adapted to exploit alternative feeding grounds as prey availability declines in the Arctic. Novel to known migration phenology, gray whales have been observed seasonally since 2018 in San Francisco Bay (SF Bay), California. We evaluated subgroup identity and mortality of gray whales in SF Bay from 2018–2025 using photo-identification. Data were collected through vessel-based surveys, opportunistic effort, and community submissions. We identified 114 individual whales of which eight were matched to a subgroup, indicating gray whales utilizing SF Bay are not merely a range extension by foraging subgroups. Only four gray whales were resighted within SF Bay between years. Using photographs, 21 individuals were successfully matched to carcasses and a minimum mortality rate of 18% was determined. Blunt and/or sharp force trauma consistent with vessel strike was determined to be the cause of death for 30 of 70 carcasses, and for nine of 11 matched animals where a cause of death was determined. Sounder and PCFG matched whales were more likely to survive SF Bay than ENP individuals, though minimum length of stay did not influence mortality. This work confirms that gray whales entering SF Bay are highly susceptible to vessel strike mortality and highlights a crucial need to identify and implement adaptive management strategies to mitigate injuries and mortality as whales continue to utilize novel habitat.

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

The migratory whale herd concept: A novel unit to conserve under the ecological paradigm - Karen K. Martien; Barbara L. Taylor; Aimée R. Lang; Phillip J. Clapham; David W. Weller; Frederick I. Archer; John Calambokidis (Marine Mammal Science, 2023)
Photographic and genetic studies have revealed the complex population structure of migratory large whales. Most research and management are geographically based, focusing on either wintering or summering areas, which in most cases fails to capture this complexity. We use examples from humpback whales ( Megaptera novaeangliae ) and gray whales ( Eschrichtius robustus ) to illustrate the concept of migratory herds, defined here as conspecific whales that migrate between the same wintering and feeding ground. In cases where individuals show strong fidelity to both feeding and wintering grounds, and therefore to a herd, dispersal between herds can be low enough to render them as demographically independent populations, where population dynamics are determined more by net internal recruitment (births minus deaths) than by immigration from outside sources. In these cases, the migratory whale herd is the appropriate unit to conserve under the ecological paradigm that focuses on groups united by demographic forces. We suggest that when addressing questions focused on ecological timescales for whale species with strong fidelity to migratory destinations, the migratory whale herd is a better initial working hypothesis rather than one based on geographically defined strata.

Oceanic giants dance to atmospheric rhythms: Ephemeral wind‐driven resource tracking by blue whales - John P. Ryan; Kelly J. Benoit‐Bird; William K. Oestreich; Paul Leary; Kevin B. Smith; Chad M. Waluk; David E. Cade; James A. Fahlbusch; Brandon L. Southall; John E. Joseph; Tetyana Margolina; John Calambokidis; et al. (Ecology Letters, 2022)
Trophic transfer of energy through marine food webs is strongly influenced by prey aggregation and its exploitation by predators. Rapid aggregation of some marine fish and crustacean forage species during wind‐driven coastal upwelling has recently been discovered, motivating the hypothesis that predators of these forage species track the upwelling circulation in which prey aggregation occurs. We examine this hypothesis in the central California Current Ecosystem using integrative observations of upwelling dynamics, forage species' aggregation, and blue whale movement. Directional origins of blue whale calls repeatedly tracked upwelling plume circulation when wind‐driven upwelling intensified and aggregation of forage species was heightened. Our findings illustrate a resource tracking strategy by which blue whales may maximize energy gain amid ephemeral foraging opportunities. These findings have implications for the ecology and conservation of diverse predators that are sustained by forage populations whose behaviour is responsive to episodic environmental dynamics.

Cetacean Strandings in the US Pacific Northwest 2000–2019 Reveal Potential Linkages to Oceanographic Variability - Amanda J. Warlick; Jessica L. Huggins; Dyanna M. Lambourn; Deborah A. Duffield; Dalin N. D’Alessandro; James M. Rice; John Calambokidis; M. Bradley Hanson; Joseph K. Gaydos; Steven J. Jeffries; Jennifer K. Olson; Jonathan J. Scordino; et al. (Frontiers in Marine Science, 2022)
Studying patterns in marine mammal stranding cases can provide insight into changes in population health, abundance, and distribution. Cetaceans along the United States West coast strand for a wide variety of reasons, including disease, injury, and poor nutritional status, all of which may be caused by both natural and anthropogenic factors. Examining the potential drivers of these stranding cases can reveal how populations respond to changes in their habitat, notably oceanographic variability and anthropogenic activities. In this study, we aim to synthesize recent patterns in 1,819 cetacean strandings across 26 species in the Pacific Northwest from 2000 to 2019 to compare with previous findings. Additionally, we aim to quantify the effects of localized and basin-scale oceanographic conditions on monthly stranding cases for five focal species using generalized additive models in order to explore potential relationships between strandings and changes in biophysical features that could affect foraging conditions or other important physiological cues. Our results suggest that strandings of harbor porpoises, gray whales, humpback whales, Dall’s porpoises, and striped dolphins are correlated with certain environmental variables, including sea surface temperature, chlorophyll concentration, and the Pacific Decadal Oscillation depending on the species. While it remains challenging to identify the causal mechanisms that underlie these relationships for a given species or population based on its utilization of such a complex ecosystem, improving our understanding of periods of increased strandings can enhance our knowledge of how these species interact with their environment and assist conservation and management efforts. This study enhances the utility of stranding records over time beyond simply reporting trends and has broader applicability to other geographic regions amid global climate change.

Comparing Uncertainty Associated With 1-, 2-, and 3D Aerial Photogrammetry-Based Body Condition Measurements of Baleen Whales - K. C. Bierlich; Joshua Hewitt; Clara N. Bird; Robert S. Schick; Ari Friedlaender; Leigh G. Torres; Julian Dale; Jeremy Goldbogen; Andrew J. Read; John Calambokidis; David W. Johnston (Frontiers in Marine Science, 2021)
Body condition is a crucial and indicative measure of an animal’s fitness, reflecting overall foraging success, habitat quality, and balance between energy intake and energetic investment toward growth, maintenance, and reproduction. Recently, drone-based photogrammetry has provided new opportunities to obtain body condition estimates of baleen whales in one, two or three dimensions (1D, 2D, and 3D, respectively) – a single width, a projected dorsal surface area, or a body volume measure, respectively. However, no study to date has yet compared variation among these methods and described how measurement uncertainty scales across these dimensions. This associated uncertainty may affect inference derived from these measurements, which can lead to misinterpretation of data, and lack of comparison across body condition measurements restricts comparison of results between studies. Here we develop a Bayesian statistical model using known-sized calibration objects to predict the length and width measurements of unknown-sized objects (e.g., a whale). We use the fitted model to predict and compare uncertainty associated with 1D, 2D, and 3D photogrammetry-based body condition measurements of blue, humpback, and Antarctic minke whales – three species of baleen whales with a range of body sizes. The model outputs a posterior predictive distribution of body condition measurements and allows for the construction of highest posterior density intervals to define measurement uncertainty. We find that uncertainty does not scale linearly across multi-dimensional measurements, with 2D and 3D uncertainty increasing by a factor of 1.45 and 1.76 compared to 1D, respectively. Each standardized body condition measurement is highly correlated with one another, yet 2D body area index (BAI) accounts for potential variation along the body for each species and was the most precise body condition metric. We hope this study will serve as a guide to help researchers select the most appropriate body condition measurement for their purposes and allow them to incorporate photogrammetric uncertainty associated with these measurements which, in turn, will facilitate comparison of results across studies.

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Assessing the Risk of Ships Striking Large Whales in Marine Spatial Planning - J. V. REDFERN; M. F. MCKENNA; T. J. MOORE; J. CALAMBOKIDIS; M. L. DEANGELIS; E. A. BECKER; J. BARLOW; K. A. FORNEY; P. C. FIEDLER; S. J. CHIVERS (Conservation Biology, 2013)
Marine spatial planning provides a comprehensive framework for managing multiple uses of the marine environment and has the potential to minimize environmental impacts and reduce conflicts among users. Spatially explicit assessments of the risks to key marine species from human activities are a requirement of marine spatial planning. We assessed the risk of ships striking humpback (Megaptera novaeangliae), blue (Balaenoptera musculus), and fin (Balaenoptera physalus) whales in alternative shipping routes derived from patterns of shipping traffic off Southern California (U.S.A.). Specifically, we developed whale‐habitat models and assumed ship‐strike risk for the alternative shipping routes was proportional to the number of whales predicted by the models to occur within each route. This definition of risk assumes all ships travel within a single route. We also calculated risk assuming ships travel via multiple routes. We estimated the potential for conflict between shipping and other uses (military training and fishing) due to overlap with the routes. We also estimated the overlap between shipping routes and protected areas. The route with the lowest risk for humpback whales had the highest risk for fin whales and vice versa. Risk to both species may be ameliorated by creating a new route south of the northern Channel Islands and spreading traffic between this new route and the existing route in the Santa Barbara Channel. Creating a longer route may reduce the overlap between shipping and other uses by concentrating shipping traffic. Blue whales are distributed more evenly across our study area than humpback and fin whales; thus, risk could not be ameliorated by concentrating shipping traffic in any of the routes we considered. Reducing ship‐strike risk for blue whales may be necessary because our estimate of the potential number of strikes suggests that they are likely to exceed allowable levels of anthropogenic impacts established under U.S. laws. Evaluación del Riesgo de Colisiones de Barcos y Ballenas en la Planificación Marina Espacial

Humpback whale abundance in the North Pacific estimated by photographic capture‐recapture with bias correction from simulation studies - Jay Barlow; John Calambokidis; Erin A. Falcone; C. Scott Baker; Alexander M. Burdin; Phillip J. Clapham; John K. B. Ford; Christine M. Gabriele; Richard LeDuc; David K. Mattila; Terrance J. Quinn; Lorenzo Rojas‐Bracho; et al. (Marine Mammal Science, 2011)
We estimated the abundance of humpback whales in the North Pacific by capture‐recapture methods using over 18,000 fluke identification photographs collected in 2004–2006. Our best estimate of abundance was 21,808 (CV = 0.04). We estimated the biases in this value using a simulation model. Births and deaths, which violate the assumption of a closed population, resulted in a bias of +5.2%, exclusion of calves in samples resulted in a bias of −10.5%, failure to achieve random geographic sampling resulted in a bias of −0.4%, and missed matches resulted in a bias of +9.3%. Known sex‐biased sampling favoring males in breeding areas did not add significant bias if both sexes are proportionately sampled in the feeding areas. Our best estimate of abundance was 21,063 after accounting for a net bias of +3.5%. This estimate is likely to be lower than the true abundance due to two additional sources of bias: individual heterogeneity in the probability of being sampled (unquantified) and the likely existence of an unknown and unsampled breeding area (−8.7%). Results confirm that the overall humpback whale population in the North Pacific has continued to increase and is now greater than some prior estimates of prewhaling abundance.

KILLER WHALES AND MARINE MAMMAL TRENDS IN THE NORTH PACIFIC—A RE‐EXAMINATION OF EVIDENCE FOR SEQUENTIAL MEGAFAUNA COLLAPSE AND THE PREY‐SWITCHING HYPOTHESIS - Paul R. Wade; Vladimir N. Burkanov; Marilyn E. Dahlheim; Nancy A. Friday; Lowell W. Fritz; Thomas R. Loughlin; Sally A. Mizroch; Marcia M. Muto; Dale W. Rice; Lance G. Barrett‐Lennard; Nancy A. Black; Alexander M. Burdin; et al. (Marine Mammal Science, 2007)
Springer et al . (2003) contend that sequential declines occurred in North Pacific populations of harbor and fur seals, Steller sea lions, and sea otters. They hypothesize that these were due to increased predation by killer whales, when industrial whaling's removal of large whales as a supposed primary food source precipitated a prey switch. Using a regional approach, we reexamined whale catch data, killer whale predation observations, and the current biomass and trends of potential prey, and found little support for the prey‐switching hypothesis. Large whale biomass in the Bering Sea did not decline as much as suggested by Springer et al ., and much of the reduction occurred 50–100 yr ago, well before the declines of pinnipeds and sea otters began; thus, the need to switch prey starting in the 1970s is doubtful. With the sole exception that the sea otter decline followed the decline of pinnipeds, the reported declines were not in fact sequential. Given this, it is unlikely that a sequential megafaunal collapse from whales to sea otters occurred. The spatial and temporal patterns of pinniped and sea otter population trends are more complex than Springer et al . suggest, and are often inconsistent with their hypothesis. Populations remained stable or increased in many areas, despite extensive historical whaling and high killer whale abundance. Furthermore, observed killer whale predation has largely involved pinnipeds and small cetaceans; there is little evidence that large whales were ever a major prey item in high latitudes. Small cetaceans (ignored by Springer et al .) were likely abundant throughout the period. Overall, we suggest that the Springer et al . hypothesis represents a misleading and simplistic view of events and trophic relationships within this complex marine ecosystem.

MOVEMENTS AND POPULATION STRUCTURE OF HUMPBACK WHALES IN THE NORTH PACIFIC - John Calambokidis; Gretchen H. Steiger; Janice M. Straley; Louis M. Herman; Salvatore Cerchio; Dan R. Salden; Urbán R. Jorge; Jeff K. Jacobsen; Olga Von Ziegesar; Kenneth C. Balcomb; Christine M. Gabriele; Marilyn E. Dahlheim; et al. (Marine Mammal Science, 2001)
A bstract Despite the extensive use of photographic identification methods to investigate humpback whales in the North Pacific, few quantitative analyses have been conducted. We report on a comprehensive analysis of interchange in the North Pacific among three wintering regions (Mexico, Hawaii, and Japan) each with two to three subareas, and feeding areas that extended from southern California to the Aleutian Islands. Of the 6,413 identification photographs of humpback whales obtained by 16 independent research groups between 1990 and 1993 and examined for this study, 3,650 photographs were determined to be of suitable quality. A total of 1,241 matches was found by two independent matching teams, identifying 2,712 unique whales in the sample (seen one to five times). Site fidelity was greatest at feeding areas where there was a high rate of resightings in the same area in different years and a low rate of interchange among different areas. Migrations between winter regions and feeding areas did not follow a simple pattern, although highest match rates were found for whales that moved between Hawaii and southeastern Alaska, and between mainland and Baja Mexico and California. Interchange among subareas of the three primary wintering regions was extensive for Hawaii, variable (depending on subareas) for Mexico, and low for Japan and reflected the relative distances among subareas. Interchange among these primary wintering regions was rare. This study provides the first quantitative assessment of the migratory structure of humpback whales in the entire North Pacific basin.

Population structure of nuclear and mitochondrial DNA variation among humpback whales in the North Pacific - C. S. BAKER; L. MEDRANO‐GONZALEZ; J. CALAMBOKIDIS; A. PERRY; F. PICHLER; H. ROSENBAUM; J. M. STRALEY; J. URBAN‐RAMIREZ; M. YAMAGUCHI; O. VON ZIEGESAR (Molecular Ecology, 1998)
The population structure of variation in a nuclear actin intron and the control region of mitochondrial DNA is described for humpback whales from eight regions in the North Pacific Ocean: central California, Baja Peninsula, nearshore Mexico (Bahia Banderas), offshore Mexico (Socorro Island), southeastern Alaska, central Alaska (Prince Williams Sound), Hawaii and Japan (Ogasawara Islands). Primary mtDNA haplotypes and intron alleles were identified using selected restriction fragment length polymorphisms of target sequences amplified by the polymerase chain reaction (PCR–RFLP). There was little evidence of heterogeneity in the frequencies of mtDNA haplotypes or actin intron alleles due to the year or sex composition of the sample. However, frequencies of four mtDNA haplotypes showed marked regional differences in their distributions (Φ ST = 0.277; P n = 205 individuals) while the two alleles showed significant, but less marked, regional differences (Φ ST = 0.033; P n = 400 chromosomes). An hierarchical analysis of variance in frequencies of haplotypes and alleles supported the grouping of six regions into a central and eastern stock with further partitioning of variance among regions within stocks for haplotypes but not for alleles. Based on available genetic and demographic evidence, the southeastern Alaska and central California feeding grounds were selected for additional analyses of nuclear differentiation using allelic variation at four microsatellite loci. All four loci showed significant differences in allele frequencies (overall F ST = 0.043; P n = 139 chromosomes per locus), indicating at least partial reproductive isolation between the two regions as well as the segregation of mtDNA lineages. Although the two feeding grounds were not panmictic for nuclear or mitochondrial loci, estimates of long‐term migration rates suggested that male‐mediated gene flow was several‐fold greater than female gene flow. These results include and extend the range and sample size of previously published work, providing additional evidence for the significance of genetic management units within oceanic populations of humpback whales.